Contextual variables and time-motion analysis in soccer - Castellano, J.; Blanco-Villasenor, A.; Alvarez, D. (International Journal of Sports Medicine, 2011)
Using a multi-camera computerised tracking system the present study aimed to provide a detailed analysis of the work-rate profile of a team of elite soccer players during official matches of the Spanish Premier League. Observation-based performance measures were obtained from 434 individual samples. 6 physical parameters involving the distance covered by players were analysed: standing intensity (0-11 km·h (-1)), low-intensity running (11.1-14 km·h (-1)), moderate-intensity running (14.1-17 km·h (-1)), high-intensity running (17.1-21 km·h (-1)), very high-intensity running (21.1-24 km·h (-1)) and sprinting (>24 km·h (-1)). These intensity thresholds were considered with respect to 4 contextual variables: match status, match location, opponent level and match half, which were analysed in relation to the effective playing time. A descriptive analysis and a multivariate mixed model were employed for the analysis of change processes in soccer. The distance total covered (m) by players at different work intensities during the effective playing time was greater when playing at home (3 931 vs. 3 887 away), when the reference team was losing (3 975 vs. 3 837 drawing and 3 921 winning) and when the level of the opposing team was higher (4 032 vs. 3 938 medium and 3 736 bottom). By contrast, their physical performance decreased during the 2nd half of matches (3 822 vs. 3 985 1st half).